1994
DOI: 10.1111/j.1476-5381.1994.tb17003.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular and gastric smooth muscle contractility by pervanadate

Abstract: 1 The contractile actions of vanadate (VO4) and pervanadate (PV, peroxide(s) of vanadate) were studied in rat gastric longitudinal muscle strips and in aortic rings. The roles of extracellular sodium and calcium were evaluated and the potential effects of nerve-released agonists were considered. The possibility that these responses were due to the potentiation of tyrosine kinase activity, as a result of PV-mediated tyrosine phosphatase inhibition was explored with the use of tyrosine kinase inhibitors (geniste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 33 publications
4
36
0
1
Order By: Relevance
“…These results imply that position 2 or 3 of the phenyl ring is not essential for the vasodilatory activity. Tyrosine kinase inhibitors, such as genistein (Akiyama et al, 1987) selectively inhibit pervanadate-induced contractions, in both gastric and aortic preparations, without causing comparable inhibition of KCl-induced contraction (Laniyonu et al, 1994). Because pervanadate mimics the action of the tyrosine kinase receptor-associated agonist epidermal growth factor, the inhibition of contractions evoked by the agonist tested in this study, is independent of the tyrosine kinase pathway.…”
Section: Discussionmentioning
confidence: 85%
“…These results imply that position 2 or 3 of the phenyl ring is not essential for the vasodilatory activity. Tyrosine kinase inhibitors, such as genistein (Akiyama et al, 1987) selectively inhibit pervanadate-induced contractions, in both gastric and aortic preparations, without causing comparable inhibition of KCl-induced contraction (Laniyonu et al, 1994). Because pervanadate mimics the action of the tyrosine kinase receptor-associated agonist epidermal growth factor, the inhibition of contractions evoked by the agonist tested in this study, is independent of the tyrosine kinase pathway.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, vanadate was found to augment free intracellular Ca 2+ in smooth muscle cells, thereby promoting increased vascular tone and contractility (99). The increased level of tyrosine phosphorylation, typically described in the mechanism of the insulinomimetic effects of vanadium derivates (13,100), was also found to be associated with the smooth muscle contractile activities by vanadium compounds (101,102). Carr et al (103) demonstrated that protein tyrosine phosphatase (PTPase) inhibition by BMOV enhances the endothelial receptor tyrosine kinase (RTK) activity and improves collateral blood flow.…”
Section: Effect Of Vanadium Compounds On Vascular Diseasesmentioning
confidence: 98%
“…23) Several studies show that vanadium compounds stimulate smooth muscle constriction, which is mediated by activation of Rho kinase in several tissue types. [9][10][11][12][13][14][24][25][26] Mori and Tsushima showed that Rho kinase played a role in OVA-induced smooth muscle constriction using guinea pig ileal longitudinal smooth muscle; Rho kinase inhibitor Y-27632 blocked OVA-induced constriction and MLC phosphorylation. 15) Our study in rat thoracic aorta tissue also showed that OVA-induced constriction was abolished by a Rho kinase inhibitor.…”
Section: +mentioning
confidence: 99%
“…7,8) Vanadium compounds exert contractile effects on vascular and non-vascular smooth muscle, such as the guinea pig taenia coli, trachea, and gallbladder smooth muscle. [9][10][11] The contractile effects of vanadates have been considered to be due to inhibition of PTPase, 9,11,12) but not ATPase, 13,14) because genistein, a protein tyrosine kinase inhibitor, attenuates vanadateinduced constriction. Vanadate-induced muscle constriction was regulated by activation of Rho kinase-dependent signaling in ileal longitudinal smooth muscle in guinea pigs, resulting in increased phosphorylation of the myosin light chain (MLC).…”
mentioning
confidence: 99%